2023
DOI: 10.3389/fbioe.2023.1154301
|View full text |Cite
|
Sign up to set email alerts
|

Applications of MXene and its modified materials in skin wound repair

Abstract: The rapid healing and repair of skin wounds has been receiving much clinical attention. Covering the wound with wound dressing to promote wound healing is currently the main treatment for skin wound repair. However, the performance of wound dressing prepared by a single material is limited and cannot meet the requirements of complex conditions for wound healing. MXene is a new two-dimensional material with electrical conductivity, antibacterial and photothermal properties and other physical and biological prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 183 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated that incorporating 2D nanosheets into electrospun nanofibers enhances the mechanical properties of membranes and improves biocompatibility, which makes them suitable for wound dressing and scaffold applications [ 140 , 141 , 142 , 143 ]. Many researchers have investigated the significance of MXenes in wound dressing applications [ 144 , 145 ]. Among many elements, titanium carbide (Ti 2 C 2 Tx) has been used mainly for wound healing due to the antimicrobial and biocompatible nature of titanium [ 145 ].…”
Section: Biomedical Applications Of Electrospun Mxenes/polymeric Nano...mentioning
confidence: 99%
“…Previous studies have demonstrated that incorporating 2D nanosheets into electrospun nanofibers enhances the mechanical properties of membranes and improves biocompatibility, which makes them suitable for wound dressing and scaffold applications [ 140 , 141 , 142 , 143 ]. Many researchers have investigated the significance of MXenes in wound dressing applications [ 144 , 145 ]. Among many elements, titanium carbide (Ti 2 C 2 Tx) has been used mainly for wound healing due to the antimicrobial and biocompatible nature of titanium [ 145 ].…”
Section: Biomedical Applications Of Electrospun Mxenes/polymeric Nano...mentioning
confidence: 99%
“…23 As a photothermal component, MXene has attracted great interest because it exhibits internal light-to-heat conversion efficiency of nearly 100%. 24–27 Moreover, the rich surface functional terminals enable it to undergo solution treatment without damaging its inherent physical properties. This merit has made MXene a promising candidate for photothermal fillers for various materials ripe for photothermal conversion.…”
Section: Introductionmentioning
confidence: 99%
“…28 Li et al fabricated carbon fiber-MXene paper with superior photothermal/electrothermal-conversion performances and shielding from electromagnetic interference. 29 In addition, MXene has showed good biosafety for fibroblasts, 30,31 and can promote fibroblast migration. Thus, wound repair can be accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…Current therapeutic strategies, such as skin grafting, artificial dermal replacements, and growth factor injections, are often encumbered by limitations including prohibitive costs, variable prognoses, potential immunogenicity, and stringent technical demands [3]. The constraints underscore the imperative for a universally applicable, cost-effective, and efficient wound dressing capable of sustained therapeutic delivery to drive natural repair processes [4].…”
Section: Introductionmentioning
confidence: 99%